Political economy of farmer group empowerment policy to support the achievement of SDGs - Aminah, Siti; Sahab, Ali; Roikan, Roikan (Jurnal Sosiologi Dialektika, 2024)
The policy of forming and strengthening farmer groups is not a practical solution for advancing agriculture/improving farmer welfare. Strengthening institutions and empowering farmer groups is not merely a matter of agricultural economics, but of political economy. The problem is, there are many technical and non-technical obstacles that place farmer groups as actors in sustainable agricultural policy and development in accordance with SDGs #2. This study discusses the complexity of agricultural problems in Watu Lanur Village, Poco Ranakan Sub-District, East Nusa Tenggara. The less than optimal natural carrying capacity, the socio-economic conditions of rain-fed farmers and the lack of intensive assistance from the government are among the causes. Empowerment of farmer groups is hampered by subsistence ethics and socio-cultural issues (customs/traditions). This study uses qualitative methods with data collection techniques through in-depth interviews and observations of farmer groups. This study shows that the community is trying to empower itself by helping farmer groups. However, in the process, technical and non-technical obstacles are still found that do not support the community's innovation movement. The conclusion of this study is that farmer group institutions are weakened and less oriented towards implementing sustainable agriculture as a result of the establishment of farmer groups simply to fulfill formal aspects of empowering farmers in order to improve farmer welfare and less use of local knowledge in empowering farmer groups.